Molecular mechanisms of pulmonary response progression in crystalline silica exposed rats. (28th January 2017) - Sellamuthu, Rajendran; Umbright, Christina; Roberts, Jenny R.; Young, Shih-Houng; Richardson, Diana; McKinney, Walter; Chen, Bean T.; Li, Shengqiao; Kashon, Michael; Joseph, Pius
Abstract: An understanding of the mechanisms underlying diseases is critical for their prevention. Excessive exposure to crystalline silica is a risk factor for silicosis, a potentially fatal pulmonary disease. Male Fischer 344 rats were exposed by inhalation to crystalline silica (15 mg/m 3, six hours/day, five days) and pulmonary response was determined at 44 weeks following termination of silica exposure. Additionally, global gene expression profiling in lungs and BAL cells and bioinformatic analysis of the gene expression data were done to understand the molecular mechanisms underlying the progression of pulmonary response to silica. A significant increase in lactate dehydrogenase activity and albumin content in BAL fluid (BALF) suggested silica-induced pulmonary toxicity in the rats. A significant increase in the number of alveolar macrophages and infiltrating neutrophils in the lungs and elevation in monocyte chemoattractant protein-1 (MCP-1) in BALF suggested the induction of pulmonary inflammation in the silica exposed rats. Histological changes in the lungs included granuloma formation, type II pneumocyte hyperplasia, thickening of alveolar septa and positive response to Masson's trichrome stain. Microarray analysis of global gene expression detected 94 and 225 significantly differentially expressed genes in the lungs and BAL cells, respectively. Bioinformatic analysis of the gene expression data identified significant enrichment of several disease and biological function categories and canonical pathways related to pulmonary toxicity, especially inflammation. Taken together, these data suggested the involvement of chronic inflammation as a mechanism underlying the progression of pulmonary response to exposure of rats to crystalline silica at 44 weeks following termination of exposure.